Morphological variability of the sweetpotato germplasm collection of the Embrapa-Centro Nacional de Pesquisa de Hortaliças - Ritschel, Patrícia Silva; Huamán, Zósimo (Pesquisa Agropecuaria Brasileira, 2002)
The sweetpotato germplasm collection conserved by Embrapa-Centro Nacional de Pesquisa de Hortaliças was gathered by means of recollection expeditions and the duplication of the collection formerly maintained by Embrapa-Centro Nacional de Pesquisa de Mandioca e Fruticultura. The purpose of this paper was to describe and to analyze the morphological variability maintained in that collection. Three-hundred and twenty-four native accessions were evaluated, using 25 morphological characteristics. It was possible to identify 256 morphological types; 223 accessions presenting unique morphology and 33 groups of morphologically identical accessions. About 20% of the collection were made of duplications. Based on the assessment of the phenotypic diversity maintained in this collection for each descriptor used, it was considered that the collection presents a high level of polymorphism. The results were discussed in relation to their use on the organization of the germplasm collection, on the planning of the in vitro collection, of seed production fields and of the molecular characterization activities and on the management of this genetic resource at national level.
Keywords: Ipomoea batatas; genetic resources; genetic polymorphism